1991
DOI: 10.1152/jappl.1991.71.1.197
|View full text |Cite
|
Sign up to set email alerts
|

Additive effects of training and high-fat diet on energy metabolism during exercise

Abstract: This study was conducted to obtain additional information about the adaptations after 12 wk of high-fat diet (HFD) per se or HFD combined with endurance training in the rat using a two [diet: carbohydrate (CHO) or HFD] by two (training: sedentary or trained) by two (condition at death: rested or exercised) factorial design. Adaptation to prolonged HFD increases maximal O2 uptake (VO2max; 13%, P less than 0.05) and submaximal running endurance (+64%, P less than 0.05). This enhancement in exercise capacity coul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
83
3

Year Published

1996
1996
2020
2020

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(95 citation statements)
references
References 0 publications
9
83
3
Order By: Relevance
“…Both exercise training and high-fat diet consumption induce an increase in mitochondrial biogenesis in skeletal muscle (1,(5)(6)(7). Increased muscle mitochondria induced by endurance exercise training were previously thought to develop through a slow process.…”
Section: Discussionmentioning
confidence: 99%
“…Both exercise training and high-fat diet consumption induce an increase in mitochondrial biogenesis in skeletal muscle (1,(5)(6)(7). Increased muscle mitochondria induced by endurance exercise training were previously thought to develop through a slow process.…”
Section: Discussionmentioning
confidence: 99%
“…However, a number of earlier studies provided evidence that high-fat diets result in an increase in mitochondrial enzymes in muscle (11)(12)(13)(14), and we have shown that large increases in FFA induce an increase in mitochondrial biogenesis (16). Furthermore, Turner et al (15) recently reported that, as in the present study, feeding rats a high-fat diet resulted in increases in mitochondrial enzyme activities, mitochondrial respiratory chain subunit protein levels, and fat oxidation capacity in skeletal muscle.…”
Section: Discussionmentioning
confidence: 99%
“…In support of this concept, recent studies have reported that raising serum free fatty acids (FFA) by a high-fat diet in humans (8), or by feeding mice or rats high-fat diets (8)(9)(10), results in decreases in skeletal muscle peroxisome proliferator-activated receptor ␥ coactivator-1␣ (PGC-1␣) mRNA (8)(9)(10) and the mRNA levels of various mitochondrial constituents (8). In contrast, a number of earlier studies provided evidence that high-fat diets induce increases in mitochondrial marker enzymes (11)(12)(13)(14), and Turner et al (15) recently reported that a high-fat diet resulted in increases in mitochondrial biogenesis and fatty acid oxidative capacity in skeletal muscle of mice.…”
mentioning
confidence: 99%
“…The alteration in the rate of use or balance of carbohydrates and lipids, often through training or diet, can lead to increased performance. For instance, Simi et al 18 found high-fat diet acts in an additive manner with endurance training, leading to increased VO 2max and submaximal endurance in rats. High-fat diet can serve to increase the duration of moderate physical activity by sparing glycogen, the depletion of which is considered to be a cause of fatigue.…”
Section: Discussionmentioning
confidence: 99%
“…16 In untrained human beings, half the energy used to exercise at 65% of maximal oxygen consumption (VO 2 max) comes from lipids in the form of both free fatty acids and muscle triglycerides. 16 In the context of enhancing endurance performance, ingesting carbohydrates during exercise is often emphasized, but diets rich in lipids can also lead to increased performance at low or moderate intensities in rodents [17][18][19] and in humans, 20,21 although not always. 22 Recent evidence has shown that HR mice do not deplete liver or gastrocnemius muscle glycogen stores any more than controls during nightly wheel running, nor do they have elevated glycogen synthase activity.…”
Section: Introductionmentioning
confidence: 99%